Miscellaneous (Others) P-OT001. Polymyxin-induced neurotoxicity masquerading as myasthenia gravis. Issue 8 (August 2021) - Chin, Amanda X.Y.; Tan, Benjamin Y.Q.; Goh, Yihui; Sangeetha, V.; Chun Pin, Teu; Cheun Chan, Yee; Rathakrishnan, Rahul
Abstract : Introduction . We describe a patient with polymyxin-induced neurotoxicity manifesting with a myasthenia-like syndrome. Objective: With the emergence of multi-drug resistant gram- negative bacilli, the use of polymyxins have renewed relevance, especially in the treatment of nosocomial infections. Frequently reported neurological adverse effects of polymyxin include paraesthesias, polyneuropathy and ataxia. Rarely, it can cause weakness secondary to neuromuscular blockade. Methods . We present a patient who had ventilation-dependent respiratory failure following polymyxin use. Results . A 62-year-old male was admitted for cholecystitis complicated by multi-drug resistant Escherichia Coli bacteraemia. Five days after initiation of polymyxin B, he developed two episodes of hypercarbic respiratory failure leading to recurrent cardiac arrests. Neurological examination revealed bilateral ptosis and fatiguable proximal weakness (proximal power MRC grade 1, distal power MRC grade 4), suggestive of a neuromuscular junction pathology. Repetitive nerve stimulation (RNS) revealed a decremental response and a characteristic U- shaped envelope pattern. The patient was started on a course of intravenous immunoglobulin due to concerns of myasthenic crisis unmasked by polymyxin, which was also promptly discontinued given the differential diagnosis of polymyxin-related neurotoxicity. Within 48 hours, he rapidly improved. Five days after cessation of polymyxin, he had full strength and complete resolution of ptosis. Interval RNS performed at this juncture normalised and acetylcholinesterase receptor antibodies returned negative. Further history taken after recovery revealed that he did not have history of droopy eyelids, diplopia or weakness prior to this presentation. Conclusion . Whilst few studies have highlighted weakness and respiratory failure from neuromuscular blockade as adverse effects of polymyxin, majority of these cases were reported between 1962 and 1973. With the renewed use of polymyxin in the era of antimicrobial resistance, physicians should have heightened awareness of this potentially serious complication. The clinical features of polymyxin-induced neurotoxicity may be difficult to distinguish from myasthenic crisis. Recognition and prompt discontinuation of polymyxin is essential.